Evaluation of tissue reaction to Aroeira (Myracrodruon urundeuva) extracts: a histologic and edemogenic study - Alessandra Cury Machado; Eloi Dezan Junior; João Eduardo Gomes-Filho; Luciano Tavares Angelo Cintra; Denise Belucio Ruviére; Renata Zoccal; Carla Andreotti Damante; Elerson Gaetti Jardim Junior (University of São Paulo, 2012)
OBJECTIVES: This study evaluated subcutaneous tissue response to Aroeira (Myracrodruon urundeuva) extract employing edemogenic and histological analyses. MATERIAL AND METHODS: Test groups consisted of aqueous and ethanolic Aroeira extracts and saline (control). For edema quantification, 18 rats received an intravenous injection of Evan's Blue. After 30 min, the extracts and saline were injected on the dorsum of the rats, which were then sacrificed after 3 and 6 h. Readings were performed in a spectrophotometer. For subcutaneous implantation, 30 rats received a polyethylene tube containing the extracts on their dorsum and then they were killed after 7 and 28 days. The samples were processed for histological analysis and evaluated with a light microscope. The inflammatory infiltrate was quantified. RESULTS: There were no statistically significant differences between aqueous extract and saline groups in relation to edema quantification in the different periods (p>0.05). Ethanolic solution resulted in more edema independently of the experimental period (p<0.05). Histological analysis showed similar results on the 7-day period for the 3 groups. There was a notable reduction on inflammatory cell number for saline and aqueous extract groups at 28 days. CONCLUSION: The aqueous extract showed biocompatible properties similar to those of saline.